The application of the Theory of Constraints Thinking Process to manufacturing managers in implementing change - Hutchin, Charles E. (Cranfield University, 1999)
This research is concerned with the problems faced by managers within manufacturing when they are expected to successfully implement a major change within their organisation. It uses, as the vehicle for the research, the Theory of Constraints Thinking Process (TOC/TP) first developed by Dr Goldratt between 1986 and 1994. The TOC is used by managers to determine what requires to be changed within their organisation and then to develop both the solution and the implementation strategy. The research has used the access obtained by the researcher to examine the approaches adopted by manufacturing managers in implementing improvement projects, which involve significant change. The primary focus of the research was to confirm the existence of a significant barrier to change and to determine whether this was a function of the individual. Once the obstacle had been identified in specific situations, the second step was to consider whether the obstacle could be described in a generic form with application to a much wider range of change environments. The final stage was to replicate the exploratory stage in other companies in other countries through the involvement of colleagues of the researcher and then consider what might be included in any change project, which would overcome the obstacle so defined. The primary method of data collection was through the application of action research and the development of the data in the form of case studies. The number and types of companies that took part in the study and the range of countries was intended to ensure a reasonable spread of data. The results suggest that one of the key obstacles to change is that outlined in the research problem and that the TOC/TP, through the use of the cloud technique, can describe this obstacle and give direction to the way of successfully dealing with it.